Agronomic response of two tomato varieties (Solanum lycopersicum L.) to the application of the biostimulant whit chitosan - Rivas-García, Tomás; Luis Gustavo Gonzalez-Gomez,; Boicet-Fabré, Tony; Jiménez-Arteaga, María Caridad; Falcón-Rodríguez, Alejandro Bernardo; Terrero-Soler, Julio César (REVISTA TERRA LATINOAMERICANA, 2021)
Chitosan has properties that promote growth and nutrition of crops. It is a biostimulant that in previous studies it demonstrated activity as growth regulator, germination and vigor promoter of plants, and yield increaser. In this work, it was evaluated the individual or combined effect of the application of chitosan by seed imbibition and foliar administration at the beginning of flowering on the agronomic response (growth, development and yield) of two varieties ESEN and L-43, established in f ield conditions with a block design at random with three replicates. The results show that the combined treatment of chitosan on the seeds in doses of 1 g L-1 and at the beginning of flowering in doses of 300 mg ha-1 promotes the evaluated variables associated with yield, and increasing this up to 60.9 Mg ha-1 in the ESEN variety and up to 27 Mg ha-1 in the L-43 variety, which represents an increment of 28.5 and 25% respectively, in comparison with the control treatment. It is concluded that the biostimulant chitosan applied as combined treatment during seed imbibition and foliar via at the beginning of flowering has signif icant results improving the variable number of flowers for plants, number of fruits, mass of the fruits and yield for both varieties in comparison with the treatment control, being obtained yield among 47‑60.9 Mg ha-1 when applying chitosan for single 42‑43 Mg ha-1 in the treatment control.